2017
DOI: 10.24843/jekt.2017.v10.i02.p07
|View full text |Cite
|
Sign up to set email alerts
|

Transparansi dan Akuntabilitas Pengelolaan Keuangan Dana Desa untuk Mendorong Kemandirian Masyarakat Pedesaan

Abstract: This study aims to determine the relation between the application of transparency and accountability on village fund allocation management. The accountability applied as a way to incarnate better governance, from its planning, execution, reporting, and accountability. We uses primary data gained from questionaires and documentations. We analyze the data using descriptive statistics and tau kendall correlations. The result suggests that there are strong relations between apllication of transparency and accounta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 0 publications
1
10
0
11
Order By: Relevance
“…Meanwhile, to create an effective government, the government accountability should be established, including the village government. Villages must be prepared so that they can implement accountability in managing village financial budgets, including planning, implementation, and reporting (Fajri, 2015;Gayatri et al, 2017;Nafidah & Anisa, 2017;Riskasari, 2016).…”
Section: Government Accountabilitymentioning
confidence: 99%
“…Meanwhile, to create an effective government, the government accountability should be established, including the village government. Villages must be prepared so that they can implement accountability in managing village financial budgets, including planning, implementation, and reporting (Fajri, 2015;Gayatri et al, 2017;Nafidah & Anisa, 2017;Riskasari, 2016).…”
Section: Government Accountabilitymentioning
confidence: 99%
“…Information and open access are carried out by conveying information during deliberations up to the delivery of financial management information through the mass media. The definition of transparency is similar to that conveyed by (Fahril et al, 2014;Gayatri et al, 2017), which states that transparency is the opening of access for the community to obtain information regarding planning, implementation and accountability for managing village funds . Has il research (Gayatri et al, 2017) found that the transparency effect on the financial management of the village.…”
Section: Effect Of Transparency On Village Financial Managementmentioning
confidence: 99%
“…Dengan adanya desentralisasi fiskal, daerah otonom diuji untuk dapat menggunakan anggaran yang direncanakan sebelumnya dengan tepat guna, efektif, dan efisien, dengan tetap mengedepankan asas kebebasan yang bertanggung jawab. Desentralisasi fiskal diharapkan akan menghasilkan manfaat nyata yakni: meningkatkan partisipasi, prakarsa, dan kreatifitas masyarakat dalam membangun dan mengembangkan daerahnya demi terciptanya pemerataan pembangunan di seluruh wilayah tersebut yang sesuai dengan potensi yang dimiliki; serta memperbaiki alokasi sumber daya yang dibutuhkan untuk pembangunan kepada tingkat pemerintahan yang diyakini mengetahui seluruh potensi yang dimiliki (Gayatri et al, 2014).…”
Section: Pendahuluanunclassified